Structural heterogeneity of α-synuclein fibrils amplified from patient brain extracts - Strohäker, Timo; Jung, Byung Chul; Liou, Shu-Hao; Fernandez, Claudio O.; Riedel, Dietmar; Becker, Stefan; Halliday, Glenda M.; Bennati, Marina; Kim, Woojin S.; Lee, Seung-Jae; Zweckstetter, Markus (Nature communications, 2019)
Parkinson’s disease (PD) and Multiple System Atrophy (MSA) are clinically distinctive diseases that feature a common neuropathological hallmark of aggregated α-synuclein. Little is known about how differences in α-synuclein aggregate structure affect disease phenotype. Here, we amplified α-synuclein aggregates from PD and MSA brain extracts and analyzed the conformational properties using fluorescent probes, NMR spectroscopy and electron paramagnetic resonance. We also generated and analyzed several in vitro α-synuclein polymorphs. We found that brain-derived α-synuclein fibrils were structurally different to all of the in vitro polymorphs analyzed. Importantly, there was a greater structural heterogeneity among α-synuclein fibrils from the PD brain compared to those from the MSA brain, possibly reflecting on the greater variability of disease phenotypes evident in PD. Our findings have significant ramifications for the use of non-brain-derived α-synuclein fibrils in PD and MSA studies, and raise important questions regarding the one disease-one strain hypothesis in the study of α-synucleinopathies. Parkinson’s disease (PD) and Multiple System Atrophy (MSA) are characterized by the pathological accumulation of α-synuclein. Here the authors employ fluorescent probes, electron microscopy and NMR spectroscopy to study the properties of α-synuclein aggregates that were amplified from patient brain extracts and observe a greater structural diversity among PD patients compared to MSA patients.